2016
DOI: 10.4236/ajps.2016.76079
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Essential Oil from Three Exotic Mytaceae Species Growing in the Botanical Garden of Rio de Janeiro, Brazil

Abstract: The leaf essential oils of three Myrtaceae species: Melaleuca leucadendra, Lophostemon confertus and Ugni molinae, non-native to Brazil and growing in the Rio de Janeiro Botanical Garden, were obtained by hydrodistillation and analyzed by GC and GC-MS. Oil yields from fresh leaves were 0.76%, 0.08%, and 0.04%, respectively. Sixty-seven percent of M. leucadendra oil was made up of monoterpenes, wherein 1,8-cineole was largely predominant (49%), followed by α-terpineol (7.6%) and terpinen-4-ol (4.3%). The sesqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In this sense, Pino et al reported that the analysis of the aerial parts from M. leucadendra collected in Matanzas Province showed also 1,8-cineole (43.0%) as the main compound [ 18 ]; while the major component was viridiflorol (28.2%) in samples from Pinar del Rio Province [ 19 ]. In parallel, other reports showed the 1,8-cineole chemotype from plants growing in Brazil [ 20 ] and Egypt [ 13 ] with 48.7% and 64.3% 1,8-cineole, respectively. Nevertheless, other chemotypes have also been documented based on phenylpropanoids (namely eugenol methyl ether and ( E )- iso -eugenol methyl ether) or nerolidol chemotypes [ 16 , 17 ].…”
Section: Resultssupporting
confidence: 54%
“…In this sense, Pino et al reported that the analysis of the aerial parts from M. leucadendra collected in Matanzas Province showed also 1,8-cineole (43.0%) as the main compound [ 18 ]; while the major component was viridiflorol (28.2%) in samples from Pinar del Rio Province [ 19 ]. In parallel, other reports showed the 1,8-cineole chemotype from plants growing in Brazil [ 20 ] and Egypt [ 13 ] with 48.7% and 64.3% 1,8-cineole, respectively. Nevertheless, other chemotypes have also been documented based on phenylpropanoids (namely eugenol methyl ether and ( E )- iso -eugenol methyl ether) or nerolidol chemotypes [ 16 , 17 ].…”
Section: Resultssupporting
confidence: 54%
“…There is a third chemotype, dominated by (E)-nerolidol (> 90%), which has been described from Uttarakhand, India [37] and from Pernambuco, Brazil [38]. Chemotype I has also been found in Cuba [39] and Rio de Janeiro, Brazil [40]. They were both dominated by 1,8-cineole (43.0% and 48.7%, respectively), but these two samples were also rich in viridiflorol (24.2% and 27.8%, respectively), and therefore, may represent a subtype of chemotype I.…”
Section: Chemical Compositionsmentioning
confidence: 99%
“…They were both dominated by 1,8-cineole (43.0% and 48.7%, respectively), but these two samples were also rich in viridiflorol (24.2% and 27.8%, respectively), and therefore, may represent a subtype of chemotype I. An agglomerative hierarchical cluster analysis was carried out using the M. leucadendra leaf essential oil compositions reported in the literature [14,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] (Figure 3). The cluster analysis reveals two sub-types of chemotype I, the two sub-types of chemotype II, as described by Brophy [14], and chemotype III, the nerolidol chemotype.…”
Section: Chemical Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…α-Terpineol (α-TPN) is monoterpene alcohol that has been isolated from a variety from natural sources, such as the essential oils from Melaleuca leucadendra [ 157 ], Citrus aurantium [ 158 ] and Nepeta dschuparensis [ 159 ]. There are three isomers, α-, β-, and γ-TPN, the latter two differing only by the location of the double bond.…”
Section: Resultsmentioning
confidence: 99%